An open-label single-arm phase II study of regorafenib for the treatment of angiosarcoma. (September 2021) - Agulnik, Mark; Schulte, Brian; Robinson, Steven; Hirbe, Angela C.; Kozak, Kevin; Chawla, Sant P.; Attia, Steven; Rademaker, Alfred; Zhang, Hui; Abbinanti, Susan; Cehic, Rasima; Monga, Varun; et al.
Abstract: Purpose: Angiosarcomas represents a diverse group of aggressive high-grade vascular tumours with limited therapeutic options. We sought to determine the safety and efficacy of regorafenib, a small-molecule multikinase inhibitor, in the treatment of metastatic or locally advanced unresectable angiosarcoma. Patients and methods: In this single-arm multicentre, open-label phase II clinical trial, 31 patients were enrolled and received regorafenib 160 mg PO daily for 21 days of a 28-day cycle. The primary endpoint for the study was progression-free survival at 4 months. Secondary endpoints included overall survival, response rate, and safety. Patients (≥18 years) with an Eastern Cooperative Oncology Group (ECOG) score of 0–1, a life expectancy of at least 4 months who had progressed on at least one but no more than 4 prior lines of therapy were eligible. Results: Of the 23 patients evaluable for efficacy, 2 had a complete response (8.7%), and 2 had a partial response (8.7%), for a total overall response rate of 17.4%. Median PFS was 5.5 months, and 12/23 patients (52.2%) had a PFS of greater than 4 months. 10/31 (32.3%) patients evaluable for toxicity had a grade 3 or higher adverse events. Conclusions: Regorafenib is a safe and active treatment for refractory metastatic and unresectable angiosarcoma. Rates of adverse events were comparable to prior studies of regorafenib for other tumour types. Regorafenib, the single agent, could be considered as therapy for patients with metastatic or unresectable AS. Highlights: ORR for regorafenib in patients with relapsed/refractory AS was 17.4%. 12/23 (52%) patients had a PFS of greater than 4 months. For those who derived clinical benefits, the median PFS was 6.7 months. 10/31 (32.3%) patients had grade 3 or higher adverse events.